2012
DOI: 10.4236/jcdsa.2012.23042
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Estimation of Hydroquinone in Skin Whitening Cosmetics

Abstract: Hydroquinone has been used for decades as a skin lightening agent. Its use in cosmetics has been banned as a result of skin problems including contact dermatitis and ochronosis. A total of 22 samples of different skin whitening cosmetics were collected from local market. They were analyzed by using thin layer chromatography and HPLC for qualitative and quantitative determination of their hydroquinone contents. The hydroquinone was extracted from samples by using 96% ethanol and was subjected to TLC analysis. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 15 publications
0
13
0
5
Order By: Relevance
“…This  max is used for further quantitative spectrophotometric measurements. This  max for hydroquinone was similar to the wavelength used for other spectrophotometric measurements by different authors [12][13][14][15] Calibration curve After determination of the maximum absorption of hydroquinone (290 nm) using spectrophotometer, The absorbance was then taken at a wavelength of 290 nm and traced on the calibration curve to give the concentration of hydroquinone in each samples. The calibration curve was where C is the concentration of hydroquinone (µg/mL) and A is the absorbance.…”
Section: Estimation Of ƛMax (Maximum Absorption Of Hydroquinone)mentioning
confidence: 84%
“…This  max is used for further quantitative spectrophotometric measurements. This  max for hydroquinone was similar to the wavelength used for other spectrophotometric measurements by different authors [12][13][14][15] Calibration curve After determination of the maximum absorption of hydroquinone (290 nm) using spectrophotometer, The absorbance was then taken at a wavelength of 290 nm and traced on the calibration curve to give the concentration of hydroquinone in each samples. The calibration curve was where C is the concentration of hydroquinone (µg/mL) and A is the absorbance.…”
Section: Estimation Of ƛMax (Maximum Absorption Of Hydroquinone)mentioning
confidence: 84%
“…High performance liquid chromatography is a widely used technique for analysis of drug product and drug substances. [7][8] An extensive literature survey revealed Spectrophometric [9][10][11] , TLC [12] and HPLC [13][14][15] for the determination of Hydroquinone and the reported analytical procedure for the estimation of monobenzone in bulk sample and unit dosage forms include HPLC [16][17][18][19] , TLC [20] and Electrophoresis techniques. [21] But there is no method which describes the simultaneous determination of Hydroquinone and Monobenzone from cream dosage form meant for external application.…”
Section: Molecular Structure Of Hydroquinonementioning
confidence: 99%
“…In the present study, NLC formulation of HQ was prepared that provides effective treatment in hyper pigmentation and melasma by passing the major obstacle in skin permeation. A detailed literature survey regarding existing methods of analysis like high-performance liquid chromatography (HPLC) [10], thin layer chromatography (TLC) [11], micellar electrokinetic chromatography (MEKC) [12], and capillary electrochromatography (CEC) techniques [13] in various biological matrices revealed that these methods are expensive, more sophisticated and involves extensive skills, thus there is need to develop simple spectrophotometric method for the estimation of Hydroquinone in various dosage forms. There is one reported UV spectrophotometric method for the estimation of hydroquinone individually in liposomes using methanol [14] and other UV spectrophotometric method for the simultaneous estimation of tazarotene and hydroquinone in gel preparation [15].…”
Section: Fig 1: Chemical Structure Of Hydroquinonementioning
confidence: 99%